The realisation of Finite ‘shall’ in the short story ‘The yellow wallpaper’ and its counterparts in two of its translations into Portuguese - Rodrigues, Roberta Rego (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This paper aims to investigate the realisation of Finite ‘shall’ in the short story ‘The yellow wallpaper’and its counterparts in two of its translations into Portuguese. There was the identiﬁcation of the occurrences of Finite ‘shall’ in the source text; after that, there was the alignment of these occurrences with its counterparts in the target texts; and, then, there was a comparison between the occurrences in the corpus with a view to semantic and structural considerations. Results show that the occurrences are quite similar with regard to the semantic aspects and relatively distinct concerning the structural ones.